Place cells, navigational accuracy, and the human hippocampus. - O'Keefe, J (1998)
The hippocampal formation in both rats and humans is involved in spatial navigation. In the rat, cells coding for places, directions, and speed of movement have been recorded from the hippocampus proper and/or the neighbouring subicular complex. Place fields of a group of the hippocampal pyramidal cells cover the surface of an environment but do not appear to do so in any systematic fashion. That is, there is no topographical relation between the anatomical location of the cells within the hippocampus and the place fields of these cells in an environment. Recent work shows that place cells are responding to the summation of two or more Gaussian curves, each of which is fixed at a given distance to two or more walls in the environment. The walls themselves are probably identified by their allocentric direction relative to the rat and this information may be provided by the head direction cells. The right human hippocampus retains its role in spatial mapping as demonstrated by its activation during accurate navigation in imagined and virtual reality environments. In addition, it may have taken on wider memory functions, perhaps by the incorporation of a linear time tag which allows for the storage of the times of visits to particular locations. This extended system would serve as the basis for a spatio-temporal event or episodic memory system.